The Influence of Diorama Media on Student Learning Outcomes in Science Subjects in Elementary Schools - Usman, Usman; Jannah, Miftahul; Ramadhani, Putri Nur (Darul Yasin Al Sys, 2026)
Although science learning in elementary schools has often relied on textbooks and simple visual media, abstract topics such as the water cycle remain difficult for students to understand. This study aims to determine the effect of water cycle diorama media on the learning outcomes of fifth-grade students at UPT SD Negeri 8 Pinrang. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group. Data were collected through learning outcome tests, observation, and documentation, and were analyzed using descriptive and inferential statistics. The findings indicate that the use of water cycle diorama media had a significant effect on students’ learning outcomes. Students taught using diorama media achieved higher learning outcomes than those taught through conventional methods. The use of diorama media helped students understand the water cycle process in a more concrete, engaging, and meaningful way. These findings suggest that water cycle diorama media can serve as an alternative instructional medium for improving students’ learning outcomes in elementary science education.